Recent advancement in OMICS approaches to enhance abiotic stress tolerance in legumes - Ali, Amjad; Altaf, Muhammad Tanveer; Nadeem, Muhammad Azhar; Karaköy, Tolga; Shah, Adnan Noor; Azeem, Hajra; Baloch, Faheem Shehzad; Baran, Nurettin; Hussain, Tajamul; Duangpan, Saowapa; Aasim, Muhammad; Boo, Kyung-Hwan; et al. (Frontiers in Plant Science, 2022)
The world is facing rapid climate change and a fast-growing global population. It is believed that the world population will be 9.7 billion in 2050. However, recent agriculture production is not enough to feed the current population of 7.9 billion people which is causing a huge hunger problem . Therefore, feeding the 9.7 billion population in 2050 will be a huge target . Climate change is becoming a huge threat to global agricultural production, and it is expected to be the worst in upcoming years. Keeping in view, it is very important to breed climate-resilient plants. Legumes are considered an important pillar of the agriculture production system and a great source of high-quality protein, minerals, and vitamins. During last two decades, advancements in OMICs technology revolutionized the plant breeding and emerged as a crop-saving tool in wake of the climate change. Various OMICs approaches like Next-Generation sequencing (NGS), Transcriptomics, Proteomics, and Metabolomics have been used in legumes under abiotic stresses. The scientific community successfully utilized these platforms and investigated the Quantitative Trait Loci (QTL), linked markers through genome-wide association studies, and developed KASP markers that can be helpful for the marker-assisted breeding of legumes. Gene-editing techniques have been successfully proven for soybean, cowpea, chickpea, and model legumes such as Medicago truncatula and Lotus japonicus. A number of efforts have been made to perform gene editing in legumes. Moreover, the scientific community did a great job by identifying various genes involved in the metabolic pathways and utilizing the resulted information in the development of climate-resilient legume cultivars at a rapid pace. Keeping in view, this review highlights the contribution of OMICs approaches to abiotic stresses in legumes. We envisage that the presented information will be helpful for the scientific community to develop climate-resilient legumes cultivars.